1977
DOI: 10.1073/pnas.74.5.1800
|View full text |Cite
|
Sign up to set email alerts
|

Extended Watson integrals for the cubic lattices

Abstract: The = (4/7r2) (2 + a)2 )K(k+)K(k-) [7] (2 + a2 + a2Z)Kk)Kk) [7 [3] [3a]in which k.2 =1 ±2za(2 + a2)1/2(a4 + 2a2 + z)'/2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(47 citation statements)
references
References 1 publication
2
45
0
Order By: Relevance
“…A continuum of states is, of course, indicative of conductive behaviour. Many similar integrals -which can be exactly solvedappear in the literature 6,10 for the lattices with a cubic unit cell but not with all the sums and products of H appearing together. In particular, the last summations of cos 2x in the P -function do not appear in the canonical form in Eq.…”
Section: Is Given Bymentioning
confidence: 99%
See 1 more Smart Citation
“…A continuum of states is, of course, indicative of conductive behaviour. Many similar integrals -which can be exactly solvedappear in the literature 6,10 for the lattices with a cubic unit cell but not with all the sums and products of H appearing together. In particular, the last summations of cos 2x in the P -function do not appear in the canonical form in Eq.…”
Section: Is Given Bymentioning
confidence: 99%
“…There currently is hardly any exactly known result for this lattice, even for non-interacting models. However it was conjectured 6 that lattices with cubic cells should have a lattice Green's functions expressable in a "canonical" integral form, which, in general, can be exactly evaluated; a rationale for this proposition was later given 7 . Glasser's canonical form for the Green's function is…”
Section: Hyperkagome Latticementioning
confidence: 99%
“…We have found that these coefficients have been quoted sometimes incorrectly in the literature: The first term, I 3 (3) = A, has been expressed analytically in terms of functions [31,32] but in apparent disagreement with the correct numerical value [27,32],…”
Section: Appendix A: Derivation Of the Effective-range Expansion In Lmentioning
confidence: 99%
“…A mathematical complication here is that each term in the expansion of the principal-valued integral has to be evaluated numerically. Previously, the triple integral I 3 (z) at z = 3 + 0 was analyzed by Watson [29], and for |z| 3 was studied [27,[30][31][32] in connection to random walks on lattices and to lattice dynamics in condensed matter. The expansion about z = 3 + 0 was found to be [27,30] …”
Section: Appendix A: Derivation Of the Effective-range Expansion In Lmentioning
confidence: 99%
“…The critical value of a is given by (This integral is actually Green's integral for the cubic lattice, and has the closed form F(1/24)F(5/24)F(7/24)F(ll/24)(6)I/2/32zr3; see [24].) In the case discussed in [52] and [40] an optimal solution was proposed informally for the case a .5; our solution agrees exactly.…”
Section: Theorem 34 (Duality) V(p) >-_ V(pe) >= V(p*) If the Dual mentioning
confidence: 99%